Thermoanalytical study of praziquantel-loaded PLGA nanoparticles - Mainardes, Rubiana Mara [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Evangelista, Raul Cesar [UNESP] (FapUNIFESP (SciELO), 2006)
Polymeric nanoparticles have received great attention as potential controlled drug delivery systems. Biodegradable polymers has been extensively used in the development of these drug carriers, and the polyesters such as polylactic acid, polyglycolic acid and their copolymers as poly-lactide-co- glycolide are the most used, considering its biocompatibility and biodegradability. Thermal analysis techniques have been used for pharmaceutical substances for more than 30 years and are routine methods for screening drug-excipient interactions. The aim of this work is to use thermal analysis to characterize PLGA nanoparticles containing a hydrophobic drug, praziquantel. The results show that the drug is in an amorphous state or in disordered crystalline phase of molecular dispersion in the PLGA polymeric matrix and that the microencapsulation process did not interfere with the chemical structure of the polymer, mantaining the structural drug integrity.
Keywords: DSC; Infrared spectroscopy; Nanoparticles; PLGA; Praziquantel; TC-DTA; copolymer; drug carrier; excipient; nanoparticle; poly lactide co glycolide; polyester; polylactic acid; polymer; praziquantel; unclassified drug; biocompatibility; biodegradability; chemical structure; infrared spectroscopy; microencapsulation; thermal analysis